Enlargement of geo polymer compound material for the renovation of conventional concrete structures. (2021) - Yadav, Rajat; Kumar Singh, Pradeep; Chaturvedi, Rishabh
Abstract: Ordinary Portland cement (OPC) concrete undergoes deterioration due to the simultaneous action of mechanical (service) and thermal loads. Concrete deterioration is manifested primarily through cracking and spalling of concrete and de-bonding of rebars. In all such cases, deteriorated structural elements require efficient and successful repair materials in order to improve their serviceability. The objective of this study is to examine the efficiency of geopolymer mortar/concrete based composite as a repair material for OPC structures. In this study, geopolymer composite was prepared by mixing fly ash, ground granulated blast furnace slag (GGBS), chopped alkali resistant chopped E-glass fibers and reaction generating liquid (RGL) comprising of sodium hydroxide (NaOH), sodium silicate (Na2SiO3) and distilled water. Three weight fractions of chopped E-glass fiber (0.5%, 1%, and 1.5%) were used in the geopolymer composites, which were used in this study. The performance of these composite repair materials was examined in terms of compressive strength, split tensile strength, modulus of rupture, bond strength, impact abrasion resistance, notch beams bending test and durability test. Bond strength of the repair material with substrate concrete was determined according to ASTM C882 and the impact abrasion resistance of the repair material was evaluated using ASTM C1747 standard.